E Exploring Syllabus Design for Law Students in Teaching ESP - Muliati Asikin (Celebes Education Review, 2020)
This research explores syllabus design in teaching ESP at the third law students in Universitas Bosowa. This study is a qualitative case study research aiming to explore and describe the syllabus design for law students. This research observe syllabuses commonly used in current ESP courses and materials for law students in teaching ESP at Universitas Bosowa. The subjects of the study is one ESP lecturer and law students of the third semester in law faculty of Universitas Bosowa, which consists of 15 students. Data gathered from interview with ESP lecturer and students, observation of teaching learning process, questionnaire and documentations. The research findings reveal that there was a variety of content teaching material in designing syllabus for law students. At the first, teaching grammatical content and selecting law English topics were as the content of syllabus design at law faculty. There was the combination of syllabus types that implemented in teaching ESP at law faculty. The results of this research are expected to contribute to the improvement of the teaching ESP at law students not only in Universitas Bosowa but also in the whole country.